2017
DOI: 10.1016/j.bjorl.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conductive hearing loss on central auditory function

Abstract: The results suggest reduced auditory temporal processing ability in adults with CHL compared to normal hearing subjects. Therefore, developing a clinical protocol to evaluate auditory temporal processing in this population is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…If FMRP‐rich sensory neurons are significant targets in FXS, one might expect to see that these neurons exhibit structural and/or functional plasticity in response to changes in neuronal activity in normal brains and that such activity‐dependent plasticity is compromised when FMRP is absent. Indeed, hearing loss or abnormal hearing induced by tinnitus leads to extensive alternations in cellular properties of auditory neurons throughout the brain (Rubel and Fritzsch, ; Parks and Rubel, ; Saunders, ; Berger and Coomber, ; Tong et al, ; Ryugo, ; Bayat et al, ). In FMR1 knockout mice, auditory brainstem neurons show altered synaptic connectivity and reduced activity‐dependent regulation of ion channel expression and conductance (Brown and Kaczmarek, ; Rotschafer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If FMRP‐rich sensory neurons are significant targets in FXS, one might expect to see that these neurons exhibit structural and/or functional plasticity in response to changes in neuronal activity in normal brains and that such activity‐dependent plasticity is compromised when FMRP is absent. Indeed, hearing loss or abnormal hearing induced by tinnitus leads to extensive alternations in cellular properties of auditory neurons throughout the brain (Rubel and Fritzsch, ; Parks and Rubel, ; Saunders, ; Berger and Coomber, ; Tong et al, ; Ryugo, ; Bayat et al, ). In FMR1 knockout mice, auditory brainstem neurons show altered synaptic connectivity and reduced activity‐dependent regulation of ion channel expression and conductance (Brown and Kaczmarek, ; Rotschafer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar 5 100 lm. neurons throughout the brain (Rubel and Fritzsch, 2002;Parks and Rubel, 2004;Saunders, 2007;Berger and Coomber, 2015;Tong et al, 2015;Ryugo, 2015;Bayat et al, 2016). In FMR1 knockout mice, auditory brainstem neurons show altered synaptic connectivity and reduced activity-dependent regulation of ion channel expression and conductance (Brown and Kaczmarek, 2011;Rotschafer et al, 2015).…”
Section: Fmrp Distribution In the Mouse Brainmentioning
confidence: 99%
“…In schools, the association between learning disabilities and hearing complaints is frequent, particularly in relation to noise, with studies having shown a worse performance of this pediatric population in both behavioral and electrophysiological hearing tests (2,3) . In addition, the peripheral changes and/or a history of serous otitis media, frequent in early childhood, may compromise the maturation of the auditory pathways, with repercussions on the central auditory skills and, consequently, on the process of learning (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Conductive hearing loss (CHL) following COM may be attributed to factors such as tympanic membrane perforation, ossicular chain disruption, or middle ear space inflammation. It is well documented that long-term sensory deprivation resulting from CHL will produce irreversible changes in the anatomical and functional integrity of the central auditory system structures [13][14][15][16][17] which may lead to the outbreak of language, cognitive, psychological and emotional problems in person 18,19 . In COM cases, infection through bone erosion can also be spared out in mastoid cortex, petrous part of the temporal bone, facial nerve, lateral sinus and dura matter.…”
Section: Discussionmentioning
confidence: 99%